2012
DOI: 10.1590/s2179-64912012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Intervenção fonoaudiológica em grupo a cantores populares: estudo prospectivo controlado

Abstract: OBJETIVO: Verificar os benefícios de um programa de aperfeiçoamento vocal em grupo a cantores populares. MÉTODOS: Trata-se de estudo de intervenção, quase experimental, realizado com 37 cantores populares de ambos os gêneros, com idades entre 18 e 40 anos e qualidade vocal adaptada. Os participantes foram divididos em dois grupos: Intervenção (GI) e Controle (GC). O GI contou com 21 indivíduos que receberam orientações sobre anátomo-fisiologia do aparelho fonador, cuidados de higiene vocal e realização de exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
2
15
0
11
Order By: Relevance
“…If there islance between the respiratory support and the laryngeal mechanisms, the vocal fold vibration remains unchanged. A study carried out with popular singers verified an increase in MPT after seven speech-language intervention sessions with vocal and respiratory exercises, evidencing the benefits of respiratory and vocal synergy (30) . According to the results obtained, it is inferred that the BCP muscles evaluated by EpMAX, abdominal and intercostal, are more related to MPT measures.…”
Section: Discussionmentioning
confidence: 90%
“…If there islance between the respiratory support and the laryngeal mechanisms, the vocal fold vibration remains unchanged. A study carried out with popular singers verified an increase in MPT after seven speech-language intervention sessions with vocal and respiratory exercises, evidencing the benefits of respiratory and vocal synergy (30) . According to the results obtained, it is inferred that the BCP muscles evaluated by EpMAX, abdominal and intercostal, are more related to MPT measures.…”
Section: Discussionmentioning
confidence: 90%
“…It is known that adequate overall health conditions are needed for one's satisfactory vocal performance. Thus, it must also be considered that the study was carried out in southern Brazil, with characteristic climate that is related to a high frequency of allergic and respiratory disorders (22,23) . The ESV protocol aims to detect voice symptoms and the impact of dysphonia on individuals, being a valuable tool to complement voice assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit provided by speech therapy has been proven in other studies [22][23][24] in which the singer himself reported improvement in his voice. Speech pathologists, singing teachers but also the choristers themselves perceive positive changes in vocal aspects, as in vocal range, breath and voice projection, after being held these interventions [21][22][23][24] .…”
mentioning
confidence: 82%
“…The benefit provided by speech therapy has been proven in other studies [22][23][24] in which the singer himself reported improvement in his voice. Speech pathologists, singing teachers but also the choristers themselves perceive positive changes in vocal aspects, as in vocal range, breath and voice projection, after being held these interventions [21][22][23][24] . It can be seen that the highest score, with respect to CPIC, was in Defect subscale, followed by the Disability and Handicap; these data are equivalent to the findings of other similar studies 12,17,18,25 , in which the defect and disability subscales had higher scores than the subscale Handicap for all singers.…”
mentioning
confidence: 82%